Motyw rozstania w literaturze dla dzieci – perspektywa pedagogiczna - Kuszak, Kinga (Wydawnictwo Naukowe UAM, 2018)
The article discusses searching for solutions related to the university education of preschool and early school teachers in a time marked by intense and unpredictable changes. The fluidreality we live in poses an important challenge for those responsible for teacher training, requiring them to prepare teachers to deal with constant changes and remain open to what is yet to come. In a constantly changing reality, it is difficultto predict which competencies teachers will need in the next decades of the 21st century. It is certainly worth the effort to focus on fostering the passion and developing the personalities of future teachers working with children of preschool and early school age. The education process should also take into account the needs and expectations of the new generation of teachers, representing what the literature of the subject describes as “generation Z”. Apart from including theoretical considerations, the article is an attempt to showcase selected solutions developed at the Faculty of Educational Studies of Adam Mickiewicz University in Poznan.
Developing Teachers’ Personalities and Passion in the Fluid Reality of the 21st Century – Searching for Solutions
Keywords: teacher education; university education; teacher competencies; personality; passion; preschool and early school education